2016
DOI: 10.1093/scan/nsw129
|View full text |Cite
|
Sign up to set email alerts
|

Pictures of disgusting foods and disgusted facial expressions suppress the tongue motor cortex

Abstract: The tongue holds a unique role in gustatory disgust. However, it is unclear whether the tongue representation in the motor cortex (tM1) is affected by the sight of distaste-related stimuli. Using transcranial magnetic stimulation (TMS) in healthy humans, we recorded tongue motor-evoked potentials (MEPs) as an index of tM1 cortico-hypoglossal excitability. MEPs were recorded while participants viewed pictures associated with gustatory disgust and revulsion (i.e. rotten foods and faces expressing distaste), non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 114 publications
(155 reference statements)
7
32
0
Order By: Relevance
“…These results can be related to the fact that taste is the sense that most relates with disgust, which is the most sensitized emotion in patients with OCD and which can generate anxiety (Pineda et al, 2015;Bhikram et al, 2017;Knowles et al, 2019). These findings agree with previous studies that show that edible contaminated stimuli generate more disgust and anxiety responses than nonedible ones (Vicario et al, 2017).…”
Section: )supporting
confidence: 90%
“…These results can be related to the fact that taste is the sense that most relates with disgust, which is the most sensitized emotion in patients with OCD and which can generate anxiety (Pineda et al, 2015;Bhikram et al, 2017;Knowles et al, 2019). These findings agree with previous studies that show that edible contaminated stimuli generate more disgust and anxiety responses than nonedible ones (Vicario et al, 2017).…”
Section: )supporting
confidence: 90%
“…On the other hand, limb regions of the motor cortex do not project to OFC or insular regions. Remarkably, we have documented that tnM1 excitability is modulated by nicotine craving [11], distaste [12], and moral disgust [13], which supports a functional link between tnM1 and reward-relevant processes in humans.…”
supporting
confidence: 65%
“…Disgust is mostly characterized by sensations in the digestive system and around the throat region, which is consistent with activations observed in the anterior insula and frontal operculum. However, there is an emotion‐related inhibitory control from the PAG, amygdala, and insula on the motor cortex and supplementary motor area in situations of threat [Benarroch, ; Hassa et al, ; Vicario et al, ], which arguably may contribute to account for deactivations in our study. Of relevance, a recent transcranial magnetic stimulation study has demonstrated motor cortex inhibition at the tongue representation specifically in response to revulsion‐eliciting food pictures and disgusted facial expressions [Vicario et al, ].…”
Section: Discussionmentioning
confidence: 68%